YAP Attenuates CD8 T Cell-Mediated Anti-tumor Response - Lebid, Andriana; Chung, Liam; Pardoll, Drew M.; Pan, Fan (Frontiers in Immunology, 2020)
YAP is a transcriptional coactivator of the Hippo signaling pathway that has largely been studied for its role in the regulation of organ size during development. Recent studies have shown that YAP is upregulated in cancer cells and more recently in the T regulatory (Treg) subset of CD4+ cells, observations that suggest the factor may play a role in promoting tumor persistence and progression by. Here, we report that YAP also plays an immunoinhibitory role in the biology of CD8 T cells, especially in activated cytotoxic cells usually found in the tumor microenvironment. Our findings add further rationale for the development and use of pharmacologic inhibitors of YAP to treat cancer.